Aproaching the Economic Dimension of Sustainable Development from a Financial Perspective: A Case Study Regarding Cash-flow Analysis and the Relationsips between Cash-flow and Net Income - Vasiu, Diana Elena (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Europe 2020, a strategy for smart, sustainable and inclusive growth stresses the necessity of smart, sustainable and inclusive growth. The objectives of a sustainable economic development include sustaining economic growth, maximizing private profits and expanding markets. Considering this, economic development must based on facts, not on papers. Therefore, considering the economic dimension of sustainable development, it is important to establish if Romanian companies listed and traded on Bucharest Stock Exchange are able to obtain profit while cash is withdrawn. Even if reported in the income statement, net profit is not simultaneously charged due to accrual accounting that makes the balance sheet provide a static picture of the financial position, while the cash flow statement provides a dynamic picture of it. Therefore, the financial performance analysis based on classical indicators of performance must be accompanied by the analysis of treasury, namely of the cash flow, which provides a comprehensive assessment possibility of the financial performance, flexibility and adaptability of the economic entity, in the context of a highly competitive and often unstable environment. A positive net flows is a confirmation of the economic success of the company representing the concrete expression of the net profit and other pecuniary accumulations, interpreted as the real self-financing investment capacity, which would lead to the real asset growth and thus to the increase of the owners’ wealth.